Measuring workplace learning results : using the Kirkpatrick Model - Harikrishnan, T. (2004)
Training at the workplace is commonly accepted as the ready-made solution to organizational problems. It is however, only a solution for problems that can be resolved by training. In this paper, we would consider the ROI of training by taking into account how to design and structure a method of identifying and evidencing the benefits via quality assessment measures which takes into account the drivers (internal and external), and the requirements (operations and customer). The processes basically compare the levels of knowledge, skills, experience and attitude available at the beginning of the programme with those available at the end of such programmes. Types of evidence and the methods used to extract them would also be considered. A case study on a group of sales personnel from a multinational company shall be presented. (Author's abstract)